The Difference Sensitivity of Solvent Hot Water and Ethanol Extracts from Leaves of Rhizophora apiculata Against Bacteria Aeromonas hydrophila - M Zaky Ditiya Putra; Henni Syawal; Morina Riauwaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Rhizophora apiculata is one of the natural ingredients that are potentially as antibacterial. R. apiculata leaves contains compounds such as flavonoids, phytochemicals, these Terpenoids, tannins, saponins and is antibacterial and antimicrobial. This research was carried out in September 2018 up to March 2019 in the Laboratory of Fish Diseases and Parasites of the Faculty of Fisheries and Marine University of Riau and Organic Natural Materials Chemistry Laboratory of Faculty of Mathematics and Natural Sciences University Of Riau. The purpose of this research is to know the comparative sensitivity of R. apiculata leaves in inhibiting the growth of bacteria Aeromonas hydrophila by using solvent hot water and solvent ethanol. Test method using Sensitivity discs Kirby Bauer with the dosage used is 100%, 90%, 80%, 60% .70%, 50%, 40%, 30%, 20%, 10%, and control (Oxytetracycline). The use of the leaves R. apiculata extracted using hot water and ethanol gives a different drag zone diameter against the bacteria A. hydrophila. A solution of hot water extract of leaves of R. apiculata is more sensitive to the bacteria A. hydrophila with the average drag zone of 10.16 mm, while the solvent ethanol with drag zone average of 8.63 mm at 100% concentration. A summary of hot water extract obtained more sensitive than ethanol solvent in inhibiting the growth of bacteria A. hydrophila. Key Word : Aeromonas hydrophila, Rhizophora apiculata, Sensitivity, Phytochemical